Comparing Delinquents And Non Delinquent Siblings With Regard To Social - Keng, Chiam Heng; Gim, Chan Siok (Penerbit USM, 2004)
According to Kornhauser (1978), all the delinquency theories originated from two main delinquency models that are the Strain Model and the Control Model.The Strain Theory suggests that felt strain resulting from frustrated needs or wants, acts as motivation for deviant behaviour. According to the Social Control Theory, social resources resulting from positive bonding with significant others such as parents, conventional peer-groups and teachers in school, act as restraints on deviant behaviour.